Pengaruh lingkungan terhadap minat anak untuk melanjutkan pendidikan - Al Akbar, Ramadhana Fatahillah (Maliki Interdisciplinary Journal, 2024)
Education is one of the main pillars in the formation of future generations who are competent and able to contribute positively to society. In this context, children's interest in continuing their education is very important, as it will influence the extent to which children will develop their academic ambitions. The environment around children plays a significant role in shaping their interest in education and their academic aspirations. External factors such as family, peers, culture, social environment, and economic conditions can have a strong impact on how a child perceives education and his or her academic goals. Peer factors influence a child's interest through social influence. Cultural and community factors can also shape perceptions and values related to education. From the factors above, it can be concluded that family, peers, culture, social environment and economic factors have a significant influence on children's interest in continuing education. Therefore, there needs to be attention and support from the family, the surrounding environment, including peers, culture, social environment, and economic factors. to increase children's interest in continuing their education.